Tuning the Double Layer of Graphene Oxide through Phosphorus Doping for Enhanced Supercapacitance - Riley,DJ; Song,W; Lischner; Rocha,VG; Qin,H; Qi,J; Hadden,JHL; Mattevi; Xie,F (ACS Energy Letters, 2017)
The electrochemical double layer plays a fundamental role in energy storage applications. Control of the distribution of ions in the double layer at the atomistic scale offers routes to enhanced material functionality and device performance. Here we demonstrate how the addition of an element from the third row of the periodic table, phosphorus, to graphene oxide increases the measured capacitance and present density functional theory calculations that relate the enhanced charge storage to structural changes of the electrochemical double layer. Our results point to how rational design of materials at the atomistic scale can lead to improvements in their performance for energy storage.